Scientific-based pictorial storybook with project-based learning method for improving the critical thinking skills of elementary school students - Dini Aria Farindhani; Muhammad Nur Wangid (Jurnal Prima Edukasia, 2019)
The study aims at developing a scientific-based pictorial storybook with PjBL method for improving the critical thinking skills of the elementary school students. The research and development initiative refer to the design of Borg Gall with 10 stages of test. Then, during the conduct of the study the data were gathered by means of product assessment sheet, teacher response questionnaire, student response questionnaire and critical thinking skills test. For the data analysis, the data were analysed by means of paired t-test with significance rate 5%. The results of the study show that the scientific-based pictorial storybook with PjBL method has been feasible for improving the critical thinking skills of the elementary school students. Based on the paired t-test results with the significance rate 5% (sig. (2-tailed) = 0.000 α = 0.05), after the implementation the critical thinking skills of the students increase significantly.